The Potential for Sharia Tourism Development at Taman Pertiwi, Pendung Talang Genting Village: A Conformity Analysis with DSN-MUI Fatwa No. 108/DSN-MUI/X/2016 - Ahmad Yani; Wawan Devis Wahyu; Dafiar Syarif (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Despite the growing global demand for Muslim-friendly tourism and Indonesia's strategic role in this sector, many local tourist destinations still lack a systematic assessment of their readiness to offer sharia-compliant experiences. This study addresses this gap by analyzing the sharia tourism potential of the Taman Pertiwi Tourism Area in Pendung Talang Genting Village. The purpose of this research is to evaluate the extent to which the site's products and services align with sharia principles and international criteria such as those set by GMTI and MUI. A qualitative case study method was employed, drawing on primary data from in-depth interviews and direct observations involving site managers, local community members, and visitors, supplemented by secondary data. The main findings reveal that Taman Pertiwi has generated positive socio-economic impacts, including job creation, support for small and micro enterprises, and an environment free from vice, while offering a tranquil nature-based experience consistent with sharia values. However, significant limitations remain: poor accessibility for visitors with special needs, substandard prayer facilities with unclean ablution areas and toilets, and a complete absence of official MUI halal certification for processed local culinary products. The contribution of these findings lies in providing an evidence-based roadmap for infrastructure improvements and formalization of sharia standards, thereby helping transform Taman Pertiwi into a leading sharia-compliant destination and offering a replicable assessment framework for similar sites in other regions.